INFLUENCE OF PHYSICAL EDUCATION ON WORKABILITY (Proceedings of International Educators Conference, 2023)
Physical culture is an important part of human life, because sport improves not only physical condition, but also psychological condition. The learning process creates tension in the sensory apparatus, memory, and activates thought processes and the emotional sphere. For students, the learning process stimulates mental work, memory and mental activity, and sports help to strengthen these processes.